Social networks: meaning and transcendence to the rescue of the culture of encounter - De los Ríos-Uriarte, María Elizabeth (2024)
Human beings seek to build interpersonal relationships by nature, which has driven the rise of social networks in recent years. This article focuses on communicating the role of social networks in our daily lives and warns about the risks they pose to the construction of authentic interpersonal encounters, based on ethics, solidarity and empathy. Among the risks generated by the so-called “digital highways” are the reification of people, the denial of plurality, the digital divide between Internet users and social networks, the distortion of truth, superficiality, immediacy and the culture of anonymity. The article stresses the importance of establishing true interpersonal encounters, avoiding falling into the “throwaway culture,” and encourages welcoming the person and forming community through dialogue and tolerance. It deepens the meaning of the triad relationship-encounter-community and the importance of communicating human dignity in social networks. Finally, it invites us to transcend superficiality, building community ties and promoting actions that value the person as an end, using the networks as a means.